A comparative study on the three calculation methods for reproduction numbers of COVID-19 - Abudunaibi, Buasiyamu; Liu, Weikang; Guo, Zhinan; Zhao, Zeyu; Rui, Jia; Song, Wentao; Wang, Yao; Chen, Qiuping; Frutos, Roger; Su, Chenghao; Chen, Tianmu (Frontiers in Medicine, 2023)
Objective This study takes four COVID-19 outbreaks as examples to calculate and compare merits and demerits, as well as applicational scenarios for three calculation methods for reproduction number. Method The epidemiological characteristics of the COVID-19 outbreaks were described. Through the definition method, the next generation matrix method and the method based on the epidemic curve and serial interval, corresponding reproduction numbers were obtained and compared. Results Reproduction numbers (Reff), obtained by the definition method, of the four regions are 1.20, 1.14, 1.66 and 1.12. Through the next generation matrix method, in region H Reff = 4.30, 0.44; region P Reff = 6.5, 1.39, 0; region X Reff = 6.82, 1.39, 0; region Z Reff = 2.99, 0.65. Time-varying reproduction numbers (Rt), which attained by serial interval (SI) of onset dates, are decreasing with time. Region H reached the highest Rt = 2.8 on July 29 and decreased to Rt < 1 after August 4; region P reached the highest Rt = 5.8 on September 9 and dropped to Rt < 1 by September 14; region X had fluctuation in the Rt and Rt < 1 after September 22; Rt in region Z researched a maximum of 1.8 on September 15 and decreased continuously to Rt <1 on September 19. Conclusion The reproduction number obtained by the definition method is optimal in the early stage of epidemics with small number of cases that have clear transmission chains, to predict the trend of epidemics accurately. The effective reproduction number Reff, calculated by the next generation matrix, could assess the scale of the epidemic and be used to evaluate the effectiveness of prevention and control measures used in epidemics with large number of cases. Time-varying reproduction number Rt, obtained via epidemic curve and SI, can give a clear picture of the change in transmissibility over time, but the conditions of use are more rigorous, requiring a greater sample size and clear transmission chains to perform the calculation. The rational use of the three methods for reproduction numbers plays a role in the further study of the transmissibility of COVID-19.